Deferiprone and efonidipine mitigated iron-overload induced neurotoxicity in wild-type and thalassemic mice - Jirapas Sripetchwandee (2020)
© 2019 Elsevier Inc. Aims: We previously demonstrated that iron-overload in non-thalassemic rats induced neurotoxicity and cognitive decline. However, the effect of iron-overload on the brain of thalassemic condition has never been investigated. An iron chelator (deferiprone) provides neuroprotective effects against metal toxicity. Furthermore, a T-type calcium channels blocker (efonidipine) effectively attenuates cardiac dysfunction in thalassemic mice with iron-overload. However, the effects of both drugs on brain of iron-overload thalassemia has not been determined. We hypothesize that iron-overload induces neurotoxicity in Thalassemic and wild-type mice, and not only deferiprone, but also efonidipine, provides neuroprotection against iron-overload condition. Main methods: Mice from both wild-type (WT) and β-thalassemic type (HT) groups were assigned to be fed with a standard-diet or high-iron diet containing 0.2% ferrocene/kg of diet (HFe) for 4 months consecutively. After three months of HFe, 75-mg/kg/d deferiprone or 4-mg/kg/d efonidipine were administered to the HFe-fed WT and HT mice for 1 month. Key findings: HFe consumption caused an equal impact on circulating iron-overload, oxidative stress, and inflammation in WT and HT mice. Brain iron-overload and iron-mediated neurotoxicity, such as oxidative stress, inflammation, glial activation, mitochondrial dysfunction, and Alzheimer's like pathologies, were observed to an equal degree in HFe fed WT and HT mice. These pathological conditions were mitigated by both deferiprone and efonidipine. Significance: These findings indicate that iron-overload itself caused neurotoxicity, and T-type calcium channels may play a role in this condition.